DNA barcode sheds light on species boundaries in the common morphologically variable rove beetle Quedius umbrinus-complex that puzzled taxonomists for more than a century (Coleoptera, Staphylinidae). Issue 7 (3rd October 2021) - Salnitska, Maria; Solodovnikov, Alexey
Abstract : In the course of a long taxonomic history, Quedius umbrinus Erichson, a common West Palaearctic rove beetle, was gradually split into a dozen species before all of them, except Q. sigwalti Coiffait from Crete, were lumped back into a single species again. All these shifts were based on the intuitive evaluation of morphological variation only. We sequenced the barcoding fragment of the CO1 gene across specimens of Q. umbrinus -complex broadly covering its geographic range and performed several DNA barcode species delimitation analyses on this dataset: tree-based Bayesian inference and Maximum likelihood, as well as tree-independent character-based (PTP, GMYC) and distance-based (ABGD). Molecular clades were largely congruent among all analyses and revealed four candidate species lineages. Of them, only Q. sigwalti is easy to distinguish by morphology alone. Morphological differences between other candidate species are present, but they are weak and do not hold for all specimens. To reflect new data in the classification we reinstated Q. pseudoumbrinus Lohse (stat. res.) as a species even though it is not always distinct from Q. umbrinus Er. (stat. rev.) morphologically. Also, we described a new species Q. volkeri (sp. nov.) from the north-western Caucasus. Finally, we placed Q. angaricus Coiffat in synonymy with Q. pseudoumbrinus Lohse (syn. nov.). http://www.zoobank.org/urn:lsid:zoobank.org:act:B6E2ED11-2029-48E7-975F-060D9DA61648